Study of Constitutional Court Decision No. 35/PUU-X/2012 and Analysis of Customary Forest Management Regulations in Indonesia and Malaysia - I Made Arya Utama (Focus Journal : Law Review, 2026)
That in the Constitutional Court Decision No. 35/PUU-X/2012 stipulates that customary forests are forests located in customary areas, no longer state forests, through the Constitutional Court Decision No. 35/PUU-X/2012, the Constitutional Court stipulates that customary forests are forests located in the areas of customary law communities and changes their status so that they are no longer state forests. The urgency of this research aims to examine the Constitutional Court Decision No. 35/PUU-X/2012 and Analysis of Customary Forest Management Regulations in Indonesia and Malaysia. The research method used in this research is the normative legal research method. The results of the research show that the Constitutional Court accepted and adjudicated the request for material review of Law Number 41 of 1999 concerning Forestry. The considerations given by the Constitutional Court in the Decision of the Constitutional Court of the Republic of Indonesia Number 35/PUU-X/2012 broadly state that Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) have provided recognition and protection for the existence of customary forests in unity with the customary rights territory of a customary law community. This is a consequence of the recognition of customary law as living law that has been in place for a long time, and continues to the present day. Therefore, placing customary forests as part of state forests is a disregard for the rights of customary law communities. Furthermore, the management of customary forests in Indonesia and Malaysia has fundamental differences. Indonesia recognizes customary forests within state forest areas as "rights forests", while Malaysia applies a system in which the management of customary land and forests is more integrated with state agrarian law, especially in the regions of Sabah and Sarawak.